1993
DOI: 10.1111/j.1464-5491.1993.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Literacy: A Problem in Diabetes Education

Abstract: Eighty-five diabetic patients who were proficient in English were studied to assess the impact of educational material of varying literacy levels on patient comprehension. Two samples of available diabetes foot care material of Grade 11 and 9 readability (measured by SMOG formula) and purposely written in-house material of Grade 6 readability were used. Patients were randomized to read information of either Grade 6 and Grade 11 or Grade 6 and Grade 9 readability. Socio-demographic data and reading habits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…[2][3][4] Additionally, they are potentially effective at improving patient comprehension and influencing health behaviors, especially if they are written at appropriate reading levels for patients. [5][6][7] The Joint Commission 8 states that PEMs should be written at or below a 5 th grade reading level, and encourages hospitals to use readability tests to revise written materials in order to address the health literacy needs of all patients.…”
Section: Patient Education Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Additionally, they are potentially effective at improving patient comprehension and influencing health behaviors, especially if they are written at appropriate reading levels for patients. [5][6][7] The Joint Commission 8 states that PEMs should be written at or below a 5 th grade reading level, and encourages hospitals to use readability tests to revise written materials in order to address the health literacy needs of all patients.…”
Section: Patient Education Materialsmentioning
confidence: 99%
“…Overland et al 6 compared comprehension of diabetes education materials written at varied grade levels amongst 85 diabetic patients. Patients were randomized to read food care information at 6 th , 9 th , or 11 th grade reading levels.…”
Section: Patient Education Materialsmentioning
confidence: 99%
“…Further studies are necessary to determine whether the results of this study are generalizable to other patient populations, whether the relation results directly from problems with patient-provider communication, and whether innovative approaches to improve communication and patient education can improve outcomes. [37][38][39][40][41][42][43][44][45][46][47][48][49] …”
Section: Discussionmentioning
confidence: 99%
“…Well known barriers to optimal diabetes self-care include psychological and social factors [13] and low levels of health literacy may discourage attendance or prevent those affected from benefitting from this mode of self-management support [14][15][16][17]. Qualitative research of patient barriers to attending structured education programmes have identified: lack of information regarding DSME from health professionals, not perceiving the benefit of attendance, difficulties in access, and shame and stigma of diabetes [18].…”
Section: Introductionmentioning
confidence: 99%